Developing an educational app for students with autism - Somerton, Michelle (Frontiers in Education, 2022)
Abstract This paper describes the design and development of an app and how research based strategies and pedagogical approaches can be embedded in a digital format. The aims and scope were to; a) synthesize research findings on reading comprehension difficulties for students with autism spectrum disorder (ASD) identifying evidence-based strategies that underpin improvements; b) determine the features associated with the design of ‘quality’ educational apps; c) create a reading comprehension app for students with ASD and; d) test in applied settings. The study utilized extensive literature searches to determine key considerations for design and development of the app and trialed through employing an AB case study design, Pre and post-testing measured discrete vocabulary skills, comprehension, phonological development and reading behaviours with n = 2 participants. The process of design provides recommendations for developers and educators concerning critical pedagogical content and functionality for a specific user group.